Ammonia/ammonium removal/recovery from wastewaters using bioelectrochemical systems (BES): A review. (November 2022) - Lee, Yu-Jen; Lin, Bin-Le; Xue, Mianqiang; Tsunemi, Kiyotaka
Highlights: Removal and recovery of NH3 /NH4 + can be carried out using BES with various setups. BES recovery of NH3 /NH4 + via stripping requires aeration with large energy input. Novel BES setups and lab-scale trials of NH3 /NH4 + recovery have been outlined. Relations between reactor volume and NH3 /NH4 + recovery are yet to be studied. Microbial electrosynthesis for valorizing NH3 /NH4 + is a potential research field. Abstract: This review updates the current research efforts on using BES to recover NH3 /NH4 +, highlighting the novel configurations and introducing the working principles and the applications of microbial fuel cell (MFC), microbial electrolysis cell (MEC), microbial desalination cell (MDC), and microbial electrosynthesis cell (MESC) for NH3 /NH4 + removal/recovery. However, commonly studied BES processes for NH3 /NH4 + removal/recovery are energy intensive with external aeration needed for NH3 stripping being the largest energy input. In such a process bipolar membranes used for yielding a local alkaline pool recovering NH3 is not cost-effective. This gives a chance to microbial electrosynthesis which turned out to be a potential alternative option to approach circular bioeconomy. Furtherly, the reactor volume and NH3 /NH4 + removal/recovery efficiency has a weakly positive correlation, indicating that there might be other factors controlling the reactor performance that are yet to be investigated.